(untitled) - Slovikova, Marcela (Doprava a spoje, 2005)
In present time we can see significant decline of railway transport. Solution of this negative situation consist in transformation of railway transport. Proposals of transformation of ZSR are in compliance with principles EU. This paper is aimed at analysis of initial conditions of railway transport transformation, especially at transport systems and technologies in railway transport